Perubahan Peran Dukun Adat Dalam Pelestarian Kearifan Lokal di Desa Kandangtepus, Kecamatan Senduro, Kabupaten Lumajang - Pratama, M. Al Qautsar; Marsyidza, Marsyidza; Ramadani, Exlima; Imaniah, Fajriyatul (Pascasarjana IAIN Metro, 2024)
This journal examines the changes in the role of traditional healers in the context of preserving local wisdom in Kandangtepus Village, Senduro District, Lumajang Regency. The research aims to understand how the role of traditional healers has evolved over time and how these changes impact the preservation of local wisdom in the community of Kandangtepus Village. This study falls into the category of qualitative research employing ethnographic methods to collect data. Data were gathered through in-depth interviews, observations, and the analysis of relevant documents. The research findings reveal various typologies of traditional healers in Kandangtepus Village, namely Baby Healers, Adat Custodians, Tiban Healers, and Weton Healers. The role of traditional healers has undergone significant transformations in response to social, economic, and cultural changes in the community of Kandangtepus Village. This research contributes to the understanding of the dynamics of changes in the role of traditional healers and their implications for the preservation of local wisdom in rural communities.